Knowledge Regarding Gastritis among Late Adolescence in Central Nepal - Silwal, Sashi; Acharya, Astha; Baral, Bimala; Devkota, Anirudra; Subedee, Aadesh; Paudel, Uttam (Marsyangdi Journal, 2021)
Gastritis is an inflammation or irritation of the lining of the stomach, can be a brief and sudden illness (acute gastritis), a long-lasting condition (chronic gastritis). Gastritis is the top most common cause of morbidity. This study is designed to find out knowledge regarding gastritis among late adolescence. A descriptive research design was used for the study. A semi-structured self-administered questionnaire was used to collect the data. Data were analysed and the descriptive and inferential test was applied by using SPSS. The study finding revealed eighty percent of the participants knew the definition of gastritis,66% on risk factors, 50% respondents on causes, 23.7% on sign and symptom,56.66% on management and 48.5% respondents on complications, and 66.55% on prevention of gastritis. The level of knowledge is average in causes, signs and symptoms, management and complications. More specifically,68% of respondents had average knowledge on gastritis and 4% had excellent knowledge. The level of knowledge of respondents is statistically significant with sex (p=0.021) and socio-economic status (p=0.008). The finding of the study revealed that knowledge on gastritis is average among the respondents. So the health education is needed for students to increase their knowledge.